Assessment of abrasive resistance potential in tunneling by F - Schimazek's value [electronic resource] - 432520 Dhiya Ruzanna Ab. Wahid; Fakulti Kejuruteraan Awam (2008)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2008